2019
DOI: 10.18662/rrem/139
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence of Translator: an Integrated System of Development

Abstract: The article deals with establishing the role of emotional intelligence in the translator"s job and introduces an integrated system of its development into translators" training. The research is based on the two-staged experiment conducted with operating and would-be translators recognizing their most frequent negative emotions as well as the causes of these emotions (stress-generating factors). It proves the job of translator to be psychologically tense and the one that can be placed in the same category as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Accordingly, Alves and Gonçalves (2013) mention that verbalizing for communication will cause some alterations in the cognitive situation; moreover, translation can be explored from several points of view that can be linguistic, discursive, cultural, social, political, and emotional. Lahodynskyi et al (2019) also underscored the considerable skills for becoming a successful translator. He listed some features of good translators, including higher linguistic proficiency, extensive cultural background, analytical mind, higher proficiency in the subject matter, along with numerous significant potentials, such as outstanding memory, flexibility, and time-management skills.…”
Section: Review Of Literaturementioning
confidence: 97%
“…Accordingly, Alves and Gonçalves (2013) mention that verbalizing for communication will cause some alterations in the cognitive situation; moreover, translation can be explored from several points of view that can be linguistic, discursive, cultural, social, political, and emotional. Lahodynskyi et al (2019) also underscored the considerable skills for becoming a successful translator. He listed some features of good translators, including higher linguistic proficiency, extensive cultural background, analytical mind, higher proficiency in the subject matter, along with numerous significant potentials, such as outstanding memory, flexibility, and time-management skills.…”
Section: Review Of Literaturementioning
confidence: 97%
“…Issues of advantages of the real situation transformation into elements of simulation and into the real context were presented by (Badea, Coman, Iancu, Bucoveţchi, 2018). Peculiarities of military personnel training, namely military interpreters can include simulation of combat environment (fire shooting, sound interference, secrecy of actions) where real-life communication takes place (Lahodynskyi et al 2019). These aspects of cadets training at Military Diplomatic Academy named after Yevheniy Bereznyak and study of English Spycraft Professionalisms as a Linguistic Phenomenon were revealed in the study of Lahodynskyi et al (2018).…”
Section: Problem Statementmentioning
confidence: 99%